Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.09.11.294397
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regulation of Hippocampal Excitatory Synapses by the Zdhhc5 Palmitoyl Acyl Transferase

Abstract: Palmitoylation is the most common post-translational lipid modification in the brain; however, the role of palmitoylation and palmitoylating enzymes in the nervous system remains elusive. One of these enzymes, Zdhhc5, has previously been shown to regulate synapse plasticity. Here, we report that Zdhhc5 is also essential for the formation of excitatory, but not inhibitory synapses both in vitro and in vivo. We demonstrate in vitro that this is dependent on Zdhhc5’s enzymatic activity, its localization at the pl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…One found ZDHHC5 to be localised to the plasma membrane exclusively when palmitoylation of the C‐terminal tail was abolished [38] whereas the other found it to accumulate in cytosolic puncta [67]. Another recent study found that in neurons, the cell surface expression of ZDHHC5 C‐terminal palmitoylation mutant was significantly increased compared with wild‐type ZDHHC5 due to a decrease in ZDHHC5 turnover [68] supporting the former study [38]. A potential explanation of these conflicting results may be due to differences in the cell types used.…”
Section: Emerging Mechanisms For Zdhhc5 Regulationmentioning
confidence: 99%
“…One found ZDHHC5 to be localised to the plasma membrane exclusively when palmitoylation of the C‐terminal tail was abolished [38] whereas the other found it to accumulate in cytosolic puncta [67]. Another recent study found that in neurons, the cell surface expression of ZDHHC5 C‐terminal palmitoylation mutant was significantly increased compared with wild‐type ZDHHC5 due to a decrease in ZDHHC5 turnover [68] supporting the former study [38]. A potential explanation of these conflicting results may be due to differences in the cell types used.…”
Section: Emerging Mechanisms For Zdhhc5 Regulationmentioning
confidence: 99%
“…Palmitoylation can alter the conformation of protein transmembrane domains or cytosolic regions, regulate proteinprotein interactions, and promote association with specific membrane microdomains (28)(29)(30)(31). In neurons, palmitoylation is best known to regulate synaptic expression and clustering of adhesion molecules, vesicle release machinery, signaling molecules, and neurotransmitter receptors, as well as their scaffolds and kinases (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) (reviewed in (1,20,(45)(46)(47)). Indeed, previous estimates suggest that 41% of all synaptic proteins are substrates for palmitoylation (17).…”
Section: A Primer On Palmitoylationmentioning
confidence: 99%